SPED Teachers’ Extent of Implementing Picture Exchange Communication System: It’s Effect on the Functional Communication Skills of Learners with Down Syndrome - Nolasco, Marita Nimiah P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
People with limited or no communication skills can use the Picture Exchange Communication System, or PECS, to communicate visually. Based on an evaluation of the functional communication skills of students with Down syndrome, this study investigated the profile of the respondents, the respondents' level of implementation of the Picture Exchange Communication System for students with Down Syndrome, the level of effectiveness of using the Picture Exchange Communication System, and the connection between these variables. The descriptive correlational research method was used for the study. The study's respondents were special education teachers from various schools in NCR. The study's respondents were chosen through the use of purposeful sampling. Frequency count, percentage, mean, weighted mean, and the chi-square test were used to tabulate and evaluate the data collected. The respondents are aged 38 on average, with more females than males. The majority of the instructors has bachelor's degrees in early childhood special education. Additionally, it was discovered that these teachers had been working in the field for an average of 7 years. The picture exchange communication system for kids with down syndrome is being used by these teachers to a very high degree, according to the research on its deployment. Based on the evaluation of the functional communication abilities of students with down syndrome, the picture exchange communication system (PECS) is rated as fair or emerging in terms of its effectiveness. Significant relationship was also observed between age and the level of effectiveness, Gender and extent of implementation.